The impact of COVID‑19 pandemic on Islamic versus conventional stock markets: international evidence from financial markets - Nomran, Naji; Haron, Razali (Springer Nature, 2021)
This study employs sample t-tests and panel pooled OLS regression to investigate the impact of COVID-19 pandemic on Islamic versus conventional stock markets returns. The study uses daily data from 15 countries over the period of September 01, 2019–April 30, 2020, which covers two main periods and over four sub-periods. Findings reveal that the returns of Islamic indices begun to be positive instead of negative by mid-April 2020, while returns of conventional ones remain negative throughout the periods. Furthermore, the results suggest a negative and statistically significant impact of COVID-19 on the performance of both stock indices. Nevertheless, this impact is weak on the Islamic indices and strong on the conventional ones. Overall, the findings indicate that Islamic stock markets perform better before and during COVID-19 than the conventional ones, and the adverse impact of the pandemic on the stock markets is relatively lesser for the Islamic indices.